Peningkatan Pengetahuan Dan Keterampilan Kelompok Pedagang Tentang Evakuasi Korban Tenggelam di Belitung - Sukarna, Raden Ade; Amiruddin, Amiruddin; Ginanjar, Sammy Lazuardi (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2021)
Abstract The increase in tourist visits to aquatic attractions will increase the risk of drowning. For traders in water tourism areas who have the ability to evacuate drowning victims. This activity aims to see if there is an increase in knowledge and skills of traders in the Tanjung Kelayang Beach tourist area after participating in the drowning evacuation training. This community service methods that use training and pre-experiment with the One Group Pretest-Posttest design with participants expected to be 30 traders on Tanjung Kelayang Beach. The activity was carried out in October 2020 and analyzed with a dependent t-test. The results of the evaluation of the activities showed an increase in knowledge (28%) and skills (40%) from before and after attending the training. Statistically there was a significant difference in the mean scores of the pre-test and post-test participants (p <0.005). The conclusion of this activity, effective training can increase the knowledge and skills of participants. Further recommendations need to be formed a special team that has a special post on the island as a tourist destination, because the merchant group is only on the beach. Keywords: training, drowning evacuation, knowledge, skills